Close relationship between T helper (Th)17 and Th2 response in murine allergic contact dermatitis. (5th September 2014) - Matsushita, A.; Seike, M.; Hagiwara, T.; Sato, A.; Ohtsu, H.
Summary Background Repeated exposure to allergens induces chronic allergic lesions in the skin and a shift in the cutaneous cytokine milieu to T helper (Th)2. Aim To assess the relationships between Th17 and Th2 response during allergic contact dermatitis (ACD) in mice. Methods ACD was induced in C57BL/6 mice by single or repeated epicutaneous challenge of 2, 4, 6‐trinitro‐1‐chlorobenzene. Relationships between Th17 and Th2 response were analyzed by immunohistochemical observations and activity of cytokines on days 8 (first challenge), 18 (11th challenge), 28 (21st challenge) and 38 (31st challenge). Results On day 8, tissue levels of interleukin (IL)‐17 and IL‐22 were high, whereas tissue levels of IL‐4 and serum IgE concentration were low. Following acute contact dermatitis, mice developed chronic eczematous lesions on day 18, and gradually improved on days 28 and 38. Tissue IL‐4 and serum IgE levels corresponded to the development and improvement of chronic eczematous lesions. Numbers of Th17 cells and tissue levels of IL‐17 and IL‐22 rapidly decreased as IL‐4 and IgE levels increased on day 18. As levels of IL‐4 and IgE decreased, the number of Th17 cells and tissue levels of IL‐17 and IL‐22 increased again on days 28 and 38. On day 18, tissue levels of Th17 response‐inducing cytokines (IL‐6, IL‐23 and transforming growth factor‐β) were high, and IL‐23‐expressing cells appeared in abundance, when Th2 response was extremely high. IL‐17 injection decreased tissue IL‐4 and serum IgE levels. Conclusions Th17 correlates closely with Th2 in murine chronic ACD induced by repeated epicutaneous challenge.